2017
DOI: 10.1371/journal.pone.0176280
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the quality of DNA from various formalin-fixed paraffin-embedded (FFPE) tissues and the use of this DNA for next-generation sequencing (NGS) with no artifactual mutation

Abstract: Formalin-fixed, paraffin-embedded (FFPE) tissues used for pathological diagnosis are valuable for studying cancer genomics. In particular, laser-capture microdissection of target cells determined by histopathology combined with FFPE tissue section immunohistochemistry (IHC) enables precise analysis by next-generation sequencing (NGS) of the genetic events occurring in cancer. The result is a new strategy for a pathological tool for cancer diagnosis: ‘microgenomics’. To more conveniently and precisely perform m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 26 publications
3
69
0
3
Order By: Relevance
“…We utilised the TSO500 assay in order to understand its utility and accuracy in determining both the TMB and druggable mutation calls in cancer. One of the key challenges with patient testing [23] is the ability to take a patient biopsy sample with limited input material and produce sequencing data and mutational calls of sufficient quality in order to make decisions on target selection and drug therapy [24].…”
Section: Discussionmentioning
confidence: 99%
“…We utilised the TSO500 assay in order to understand its utility and accuracy in determining both the TMB and druggable mutation calls in cancer. One of the key challenges with patient testing [23] is the ability to take a patient biopsy sample with limited input material and produce sequencing data and mutational calls of sufficient quality in order to make decisions on target selection and drug therapy [24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, low tumor purity, which can result from infiltration of immune or tumor microenvironment cells, can lead to reduced TMB assay sensitivity. Also, fixation time is a preanalytical factor that influences the introduction of FFPE‐induced deamination artefacts, which also impacts TMB estimation at the stage of bioinformatic analysis …”
Section: Variation In Tmb Assessment and Factors That Impact Tmb Outputmentioning
confidence: 99%
“…Also, fixation time is a preanalytical factor that influences the introduction of FFPE-induced deamination artefacts, which also impacts TMB estimation at the stage of bioinformatic analysis. 58,59 For sequencing, genome coverage differs between WGS, WES, and targeted gene panel assays. WGS covers the whole genome, WES covers the entire exome coding region, and targeted gene panels cover specified areas that may or may not include tumor suppressor genes, driver genes, or intronic regions.…”
Section: Variation In Tmb Assessment and Factors That Impact Tmb Oumentioning
confidence: 99%
“…Furthermore, we observed that overnight digestion at 65°C improved the efficiency of DNA extraction from FFPE tissues. 12 Phenol chloroform extraction is the conventional method for organic extraction of nucleic acids. However, we found better extraction efficacy with phenol:chloroform: isoamyl alcohol rather than with phenol chloroform extraction (unpublished results).…”
Section: Discussionmentioning
confidence: 99%